Effect of Colocasia esculenta (Taro) Extract in the Reduction of Vulval Development in Let-60 Gene of Caenorhabditis elegans - Lacorte, Laarni Hannah; Amador, Michaela Gabrielle; Carmona, Hanz Kristen; Vera, Nicole De; Gabriel, Ricah Mae; Manigbas, Alphonsus Rey; Pascua, Diozelle; Leyble, Azilana Yddet (Asian Journal of Biological and Life Sciences, 2020)
Introduction:Different changes in the environment drives the body to adapt for survival. Exposure to toxic agents can release free radicals from cellular metabolism that serve as a medium for a healthy cell to mutate. Let-60 gene or let-23 EGFR (epidermal growth factor receptor) regulated epithelial tissue development and homeostasis. However, inappropriate activation of EGFR is driver of tumorigenesis. Taro, root vegetable whose corm is often consumed as food.Aim:Taro’s optimal protein content is investigated for its reduction properties against the development of vulva inCaenorhabditis elegans.Caenorhabditis elegansis an auxotrophic nematode that is often utilized as a representative of a mammal due to its genotypic similarities.Methods:Three concentrations, 0.5 mg/mL, 10 mg/mL and 50 mg/mL were subjected to the synchronized-growthCaenorhabditis elegans. Neither concentration utilized was toxic to the initial development of the nematode. The synchronized L1 stageC. elegansworms, which were cultivated from the nematode growth medium at 20°C, were utilized and transferred into 4 NGM plates for a more synchronized growth. The worms of L1 stage were obtained and flooded withE. coliOP50 as its food source. The worms of L1 stage were then grouped according to the concentration. The number of worms, those with and without vulva, are quantified. Results will be tabulated and Two-way mixed ANOVA was used to compare the effectiveness of the concentrations used and to analyze the significant difference between the data collected.Results: The 10 mg/mL concentration ofCaenorhabditis elegansextract yielded the greatest number of nematode sans their vulva.Conclusion:No concentration of the extract was detrimental to the viability to the nematode after 24 hr of treatment. The taro extract may have reduced the vulva inCaenorhabditis elegansat the 10 mg/mL and 50 mg/mL concentration. Among the three concentrations, the 10 mg/mL had the most significant reducing effect.
Keywords: Caenorhabditis elegans; Colocasia esculenta; Corm; Let-23 EGFR; Let-60 gene; vulva